Microbiota-derived extracellular vesicles: current knowledge, gaps, and challenges in precision nutrition - Marquez-Paradas, Elvira; Torrecillas-Lopez, Maria; Barrera-Chamorro, Luna; del Rio-Vazquez, Jose L.; Gonzalez-de la Rosa, Teresa; Montserrat-de la Paz, Sergio (Frontiers in Immunology, 2025)
The gut microbiota has co-evolved with its host, profoundly shaping the development and functioning of the immune system. This co-evolution has led to a dynamic relationship where microbial metabolites and molecular signals influence immune maturation, tolerance, and defense mechanisms, highlighting its essential role in maintaining host health. Recently, bacterial extracellular vesicles (BEVs), membrane nanoparticles produced by bacteria, have emerged as important players in gut balance and as potent immune modulators. These vesicles reflect the characteristics of the bacterial membrane and contain nucleic acids, proteins, lipids, and metabolites. They can regulate immune processes and are involved in neurological and metabolic diseases due to their ability to distribute both locally in the gut and systemically, affecting immune responses at both levels. This review provides a comprehensive overview of the characteristics and functional profile of BEVs, detailing how nutrition influences the production and function of these vesicles, how antibiotics can disrupt or alter their composition, and how these factors collectively impact immunity and disease development. It also highlights the potential of BEVs in the development of precision nutritional strategies through dietary modulation, such as incorporating prebiotic fibers to enhance beneficial BEV production, reducing intake of processed foods that may promote harmful BEVs, and tailoring probiotic interventions to influence specific microbial communities and their vesicular outputs.